SUN-LB65 Circulating Micrornas Linked to Bone Metabolism Are Affected by Sequential Anti Osteoporotic Treatment in Postmenopausal Osteoporosis - Yavropoulou, Maria (J Endocr Soc, 2020)
Depending on osteoporosis severity a long-term treatment, often in the form of a sequential regimen, may be required. The expression of microRNAs (miRs) related to bone metabolism in the serum is potentially affected by anti-osteoporotic treatment. Here, we investigated the effect of sequential treatments on microRNA expression profile in the serum. Methods: This is an observational, open label, non-randomized clinical trial that included 37 postmenopausal women with osteoporosis who were treated with denosumab (Dmab) for 1 year. Patients had been previously treated for 2 years with either teriparatide (n=20), or zolendronate (n=6), or were treatment-naïve (n=11). We evaluated changes in the relative serum expression of selected miRs linked to bone metabolism at 3 and 12 months of Dmab treatment at each group separately. Results: In the group of patients who were previously treated with teriparatide, the relative expressions of miR-21a-5p, miR-29a, and miR-2861 were significantly decreased at both 3 months (fold change 0.13, p<0.001 for miR-21a-5p; fold change 0.68, p=0.044 for miR-29a; fold change 0.16, p<.0001 for miR-2861), and 12 months (fold change 0.09, p<0.001 for miR-21a-5p; fold change 0.65, p=0.044 for miR-29a; fold change 0.19, p<0.001 for miR-2861) of Dmab treatment. The relative expression of miR-23a-3p was also significantly decreased (fold change 0.65, p<0.001) at 12 months of Dmab treatment. The relative expression of miRs was not changed among patients previously treated with zolendronate. No change was also observed during Dmab treatment in previously treatment-naïve osteoporotic women. Conclusions: The expression of circulatings miRs linked to bone metabolism during Dmab treatment is depended on previous treatment status. Patients previously on teriparatide treatment present alterations of the relative expression of miRs related to the expression of key osteoblastic genes such as RUNX-2 (miR-23), collagen type 1 (miR-29a) and HDAC5 gene (miR-2861) during subsequent treatment with Dmab Our data suggest that teriparatide may influence the subsequent anti-resorptive effect of Dmab on bone metabolism at post-transcriptional level.